Draft Annual Plan 1996-97 Government of Madhya Pradesh - Planning Commission (Planning Commission, 1996)
It is significant to note that the contribution of primary sector in the net State domestic product has come down from 55.31 percent in 1980-81 to 43.44 percent in 1994-95, whereas that of both secondary and tertiary sectors have increased from 18.25 and 26.44 percent, respectively in 1980-81 to 23.63 and 32.43 percent respectively in 1994-95. In spite of the falling contribution of the primary sector, the work-force engaged in this sector has not declined appreciably. Still about 77.54 percent of the main workers are engaged in the primary sector.
Government of Madhya Pradesh, Planning, Economics and Statistics Department